Post-infection symptoms up to 24 months after COVID-19: a matched cohort study in Berlin, Germany - Meierkord, Anne; Schulze, Daniel; Gertler, Maximilian; Seybold, Joachim; Mall, Marcus A.; Kurth, Tobias; Mockenhaupt, Frank P.; Theuring, Stefanie (Frontiers in Public Health, 2025)
IntroductionLong-term health consequences after mild COVID-19 are not well described. Our aim was to estimate their prevalence and describe the time course of signs and symptoms for a period of up to 24 months after SARS-CoV-2 infection.MethodsWe conducted a cohort study matched for age, sex, and test week among individuals who had attended the public COVID-19 test center at Charité—Universitätsmedizin Berlin, Germany. In early 2022, 576 former COVID-19 patients (>95% non-hospitalized) and 302 uninfected individuals responded to a questionnaire on retrospective monthly symptoms since the test date up to 24 months ago.ResultsSymptoms compatible with long COVID were present in 42.9% (247/576) of former COVID-19 patients, compared with 21.2% (64/302) in the uninfected group. In former patients, unadjusted odds ratios (OR) were highest for disturbed taste/smell (OR 9.1 [95% CI: 4.0–21.1]), memory difficulties (OR 5.1 [95% CI: 2.9–8.9]), and shortness of breath at rest (OR 4.5 [95% CI: 1.9–10.6]). In most former COVID-19 patients, symptoms occurred in one coherent period and resolved after a median of 6.5 months, while taste/smell disturbance and neurological/cognitive symptoms showed longer times until recovery. Factors associated with long COVID-compatible symptoms included hospitalization, symptomatic COVID-19 infection, low household income and female sex.ConclusionPost-infection symptoms in mild COVID-19 patients mostly persist for about half a year, but sometimes longer. Among uninfected individuals who never experienced COVID-19, 21.2% also reported long COVID-compatible symptoms. The current long COVID definition might require revision to prevent misclassification and over-reporting, and to improve diagnosis and prevalence estimates.